Rejuvenation of the Arabic Learning Paradigm: Considering Richard Rorty's Idea as an Alternative Education Discourse - Afif Amrullah (Pasca Sarjana IAIN Sultan Amai Gorontalo, 2024)
The purpose of this study is to show the educational aspects of Richard Rorty's thought that are linked to Arabic language education. This research is a type of document analysis that identifies and selects data in the form of text, then checks, sorts and evaluates the core concepts of Rorty's thinking systematically to be able to understand and interpret it in the context of learning Arabic. The research method used is literature research. Data analysis is carried out through three stages, namely data reduction, data presentation and conclusion drawn/verification. The results of the study show that Rorty's Paradigm of Thinking touches on several important aspects about the purpose and method of language teaching. In Rorty's view, the function of language as a means of communication, Rorty emphasizes the role of language as a tool for social interaction and conveying meaning. In language education, Rorty's educational paradigm challenges an approach that focuses on teaching rigid and normative grammar. In addition, he emphasized the importance of education as a social construction process where students not only learn language, but also develop their perspective on the world and the way they interact with others. Thus, Rorty's thinking in relation to language education emphasizes creativity, social and cultural context, as well as a growing understanding of language and meaning.